Pengaruh Ukuran Perusahaan dan Corporate Governance Terhadap Kinerja Keuangan Dengan Pengungkapan Sustaunability Report Sebagai Variabel Intervening - Ananda Muliaturrohmah Ikhwani; Irma Paramita; Karsam Sunaryo (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
Financial performance can provide an overview of past performance and future prospects of a company. Many companies carry out business activities related to nature but do not disclose sustainability reports. Companies that have a large company size should disclose more information than small companies, including disclosures about the implementation of Corporate Governance and sustainability reports disclosure. With these disclosures of information, it is expected to increase public trust in the company and improve the company's financial performance. This research aims to obtain evidence that company size and Corporate Governance influence financial performance, and the role of Sustainability Report disclosure as mediating the relationship between these variables in nine state-owned enterprises and the mining sector for five years (2013-2017). The results of this study indicate that (1) company size has effects on financial performance; (2) audit committee has effects on financial performance; (3) the board of directors does not affect financial performance; (4) company size has not affect the disclosure of sustainability report; (5) the audit committee has not affect the disclosure of sustainability report; (6) the board of directors has effect the disclosure of sustainability report; and (7) Sustainability Report disclosure can’t mediate the influence between company size/Corporate Governance on financial performance.